“LANGUAGE AND IDENTITY: HOW ENGLISH REFLECTS CULTURAL DIVERSITY” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the relationship between language and identity through the example of English as a global language. It explores how English reflects cultural diversity, adapts to different societies, and serves as a tool of communication among various ethnic and linguistic groups. The study emphasizes that while English connects people worldwide, it also carries traces of local cultures, traditions, and values. The findings reveal that English is not a single, uniform language but a dynamic system representing multiple identities and worldviews.